Hungarian Monitoring, 13 May 1989 . [Magyar rádiófigyelő], 1989. május 13 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Bush promises economic concessions for Soviet democratization and disarmament - Honecker on reform processes in some socialist countries - Shevardnadze's talks in Bonn - More tensions in Karabakh hill region - Two Soviet detectives allegedly have proof against Yegor Ligachev - Paris officially protests Romanian rights infringements Domestic Affairs: - Ministerial council decides to suspend Nagymaros dam construction works with immediate effect - International conference on the future of Europe - On international, multi-party roundtable conference on the future of Europe held in Budapest - Party spokesman on the state of Kádár's health - Interview with Miklós Németh on reforming the government, the government's work and financial support for newly organizing parties - Two members of Marxist Centrum, docent Ida Vass and János Sántha, judge 1956 to have been a counter-revolution - Conversation with Ágnes Heller and Ferenc Fehér on how their fates took shape, and their publications - Interview with István Szabó, first secretary of Szolnok County Party committee on corruption in the county - Interview with László Maróthy on his career characteristic of the Kádár era - Debate between Hungarian Socialist Workers' Party (MSZMP) and Opposition Roundtable representatives over talks Economy: - Ádám Angyal, managing director of Ganz-Danubius Ship and Crane Works on restructuring the industry Külpolitika: - Bush gazdasági kedvezményeket ígért a SZU-nak demokratizálásért és leszerelésért - Honecker az egyes szocialista országokban végbemenő reformfolyamatokról - Sevardnadze bonni tárgyalásai - Újabb feszültségek a Karabah-hegyvidéken - Két szovjet nyomozónak állítólag bizonyítékai vannak Jegor Ligacsov ellen - Párizs hivatalosan tiltakozott a romániai jogsértések miatt Belpolitika: - A Minisztertanács úgy döntött, hogy azonnali hatállyal felfüggeszti a nagymarosi vízlépcső építési munkálatait - Nemzetközi konferencia Európa jövőjéről - Az Európa jövőjéről Budapesten tartott nemzetközi, sokpárti kerekasztal konferenciáról - Major pártszóvivő Kádár egészségi állapotáról - Interjú Németh Miklóssal a kormányátalakításról, a kormányzati munkáról és az újonnan szerveződő pártok anyagi támogatásáról - A Marxista Centrum két tagja, Vass Ida docens és Sántha János úgy ítélik meg, hogy 1956 ellenforradalom volt - Beszélgetés Heller Ágnessel és Fehér Ferenccel sorsuk alakulásáról és publikációikról - Interjú Szabó Istvánnal, a Szolnok megyei pártbizottság első titkárával a megyében meghonosodott korrupcióról - Interjú Maróthy Lászlóval a Kádár-korszakra jellemző karrierjéről - Vita a tárgyalások körül az MSZMP és az Ellenzéki Kerekasztal képviselői között Gazdaság: - Angyal Ádám, a Ganz-Danubius Hajó és Darugyár vezérigazgatója a szerkezetváltásról